2013
DOI: 10.1371/journal.pgen.1003933
|View full text |Cite
|
Sign up to set email alerts
|

MYB97, MYB101 and MYB120 Function as Male Factors That Control Pollen Tube-Synergid Interaction in Arabidopsis thaliana Fertilization

Abstract: Pollen tube reception involves a pollen tube-synergid interaction that controls the discharge of sperm cells into the embryo sac during plant fertilization. Despite its importance in the sexual reproduction of plants, little is known about the role of gene regulation in this process. We report here that the pollen-expressed transcription factors MYB97, MYB101 and MYB120 probably control genes whose encoded proteins play important roles in Arabidopsis thaliana pollen tube reception. They share a high amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 40 publications
4
97
0
Order By: Relevance
“…To examine if these genes are also abundantly expression in the male organ of other plant species, we were able to identify the Arabidopsis and rice (Oryza sativa) homologs of GaMYB (MYB101/ AT2G32460 and Os01g0812000) and found that the pMYB101::GUS is specifically expressed in the pollen grain and the Arabidopsis triple mutant myb101 myb97 myb120 exhibits defects in pollen function (Liang et al, 2013). There is no detailed study of the ADIPOR-like homologs in Arabidopsis or rice, nor could we reliably identify a homolog of F. vesca CNG channel a3 in Arabidopsis or rice.…”
Section: Identification Of Gametophyte and Sporophyte Genesmentioning
confidence: 99%
“…To examine if these genes are also abundantly expression in the male organ of other plant species, we were able to identify the Arabidopsis and rice (Oryza sativa) homologs of GaMYB (MYB101/ AT2G32460 and Os01g0812000) and found that the pMYB101::GUS is specifically expressed in the pollen grain and the Arabidopsis triple mutant myb101 myb97 myb120 exhibits defects in pollen function (Liang et al, 2013). There is no detailed study of the ADIPOR-like homologs in Arabidopsis or rice, nor could we reliably identify a homolog of F. vesca CNG channel a3 in Arabidopsis or rice.…”
Section: Identification Of Gametophyte and Sporophyte Genesmentioning
confidence: 99%
“…In the triple myb mutant, the pollen tube coils in the female gametophyte and fails to discharge sperm cells (Leydon et al, 2013;Liang et al, 2013), demonstrating an active role for the pollen tube in pollen tube reception. Loss of AUTO-INHIBITED Ca 2+ ATPASE9 (ACA9), which encodes a calcium efflux pump, results in some pollen tubes failing to discharge the sperm, even though they reach the synergid and arrest growth in the synergid cell; thus, aca9 tubes differ from triple myb mutant tubes in that they fail to coil and burst (Schiøtt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…When pollen tubes enter ovules lacking this signaling system, they continue to grow, forming a coil. A triple mutant lacking three Myeloblastosis (MYB) transcription factors (MYB97, MYB101, and MYB120) is the only pollen mutant described with the complementary loss of function phenotype (failure to stop growing and discharge sperm upon contact with the female gametophyte; Leydon et al, 2013;Liang et al, 2013). It has been proposed that myb triple mutant pollen tubes fail to produce signaling molecules sensed by the female FER, LRE, NTA system; however, this has not yet been demonstrated.…”
mentioning
confidence: 99%